Re‐examining the implications of COVID‐19 on the Canadian dairy and poultry sectors. (28th April 2021) - Weersink, Alfons; von Massow, Michael; McDougall, Brendan; Bannon, Nicholas
Abstract: The dairy and poultry sectors responded quickly to the initial adjustments in the quantity and nature of food products forced by the shuttering of the hospitality sector and the subsequent switch to buying food from grocery stores. In addition, these sectors were less affected by the labor availability and health issues from COVID‐19 (coronavirus disease‐2019) that plagued others, such as red meat processors. While the overall impacts were less than most other parts of the agri‐food system, some elements of supply managed products, particularly poultry processors, have experienced a reduction in returns and are still adjusting to the new demand and supply situation. The extent of the impact is correlated with the degree to which the supply chain further upstream was connected to the downstream hospitality sector. Résumé: Les secteurs du lait et de la volaille ont réagi rapidement aux ajustements initiaux en termes de quantité et de la nature des produits alimentaires imposés par la fermeture du secteur de l'hôtellerie et le passage subséquent à l'achat de produits alimentaires en épicerie. En outre, ces secteurs ont été moins touchés par la disponibilité de la main‐d'oeuvre et les problèmes de santé liés à la COVID‐19 comparativement à d'autres, comme les transformateurs de viande rouge. Bien que les impacts globaux aient été inférieurs à ceux de la plupart des autres éléments du système agroalimentaire, certains secteurs sous gestion de l'offre, en particulier les transformateurs de volaille, ont connu une réduction des rendements et s'adaptent toujours à la nouvelle situation de l'offre et de la demande. L'ampleur de l'impact est corrélée avec le niveau de dépendance entre la chaîne d'approvisionnement plus en amont et l'industrie hôtelière en aval.